Analysis of the 2007-2008 Hérault premiumized grubbing-up campaign: A tool to better understand Fischer-Boel's 2008-2011 grubbing-up campaigns and the desire in 2022 to reintroduce locally premiumized grub-ups - Étienne Montaigne; Samson Zadmehran; Alfredo Manuel de Jesus Oliveira Coelho; Yacine Messaoudène (Wine Economics and Policy, 2023)
In 2022, in Bordeaux due to a structural oversupply, grape growers' syndicates have asked to reimplement premiumized grub-ups in order to bring the market back to equilibrium. However, in today's CMO no legal basis exists to conduct such a policy. In this article, we go over the policy of planting rights (transformed in 2016 into planting authorization) and of premiumized grub-ups. In undertaking this historical review of Europe's grubbing-up policy, we analyze in detail Pierre Bartoli's 1982 thesis and studies of the Observatoire de l'Hérault (Dyopta) that take into account experts' opinions and statistical viewpoints. This review enables us to present the main indicators in order to 'objectively' analyze data that we received from a 2007/2008 grubbing-up campaign in Hérault. Our originality is the analysis of a subset consisting of 341 Viniflhor applications for grubbing-up premiums, which represents 20% of all beneficiaries receiving premiums. The applications were later sent with the applicants' consent to a development agency that transmitted them to us. Within this subset, we selected 51 grape growers with whom we conducted a qualitative and quantitative survey. Our goal was to identify their real motivations for grubbing up their vines. We then put forward synthesized results explaining the qualitative interviews and run the data through an econometric model. The main results are that many grape growers grubbed up only a small fraction of their vineyards mainly to cash in on the premiums in times of dire wine crisis. Grubbing ups of young 'improving varietals' reinforces this analysis. Furthermore, the 2007/2008 grubbing-up campaign comes a year just before the 2008/2011 Fischer-Boel grubbing-up campaigns that wanted to reduce Europe's vineyard of 175,000 ha of vines by eliminating the least efficient grape growers. We thought it would be interesting to shed light on this 2008 wine CMO policy by using the results of the 2007/2008 grubbing-up campaign.
Keywords: 330; CAP Reform; FADN; sustainability; wine sector